A rational approach between vitamin d, immunomodulation and the renin-angiotensin system linked to prevention and treatment of severe acute respiratory syndrome by COVID-19 - Martín Giménez, Virna M. (2021)
A distinctive feature of COVID-19 is its low mortality rate, where the leading cause of decease is related to the development of severe acute respiratory syndrome (SARS). This syndrome involves an exacerbated inflammatory reaction, frequently known as cytokine storm, mainly in the lungs and concomitant over activation of the renin-angiotensin-aldosterone system (RAAS). Consequently, this "explosive cocktail" can lead to death or permanent respiratory sequelae in patients infected with SARSCoV- 2. In this sense, multiple therapeutic strategies have been proposed. Among them, vitamin D stands out as it exerts numerous immunomodulatory effects by acting on various types of immune and epithelial cells, in addition to being able to stimulate the protective arm [(ACE2/Ang- ( 1-7)] and inhibit the damaging arm (ACE/Ang-II) of the RAAS. Therefore, in the present mini-review, some of the main mechanisms underlying these effects mediated by vitamin D and its receptors are analyzed. Knowledge and translational projection of these mechanisms would positively influence the prevention and treatment of SARS. Thus, current evidence on vitamin D and COVID-19 adds arguments to rational therapy regarding reducing or avoiding disease progression and improving prognosis.